2011
DOI: 10.4236/jbnb.2011.22024
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of biocompatible magnetic microspheres with chitosan

Abstract: Microsphere is a term used for small spherical particles, with diameters in the micrometer range (typically 1 μm to 1000 μm (1 mm)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The results of FT-IR spectra strongly match those mentioned by Jiang et al [41] who indicated the presence of stretching vibrations of hydroxyl peak at 3427 cm −1 and the occurrence of strong peaks at 2925 and 2855 cm −1 confirmed the existence C-H stretching vibration of the polymer backbone. Similarly, Nasra et al [42] reported that the stretch vibrations of C-O are located at 1084 and 1032 cm −1 . For cross-linked chitosan microspheres, the existing of an additional peak at 1656 cm −1 , which clarifies stretching vibrations of the C=N bond, emphasizes the formation of Schiff's base as a result of the reaction.…”
Section: Characterization Of Chitosan Beadsmentioning
confidence: 84%
“…The results of FT-IR spectra strongly match those mentioned by Jiang et al [41] who indicated the presence of stretching vibrations of hydroxyl peak at 3427 cm −1 and the occurrence of strong peaks at 2925 and 2855 cm −1 confirmed the existence C-H stretching vibration of the polymer backbone. Similarly, Nasra et al [42] reported that the stretch vibrations of C-O are located at 1084 and 1032 cm −1 . For cross-linked chitosan microspheres, the existing of an additional peak at 1656 cm −1 , which clarifies stretching vibrations of the C=N bond, emphasizes the formation of Schiff's base as a result of the reaction.…”
Section: Characterization Of Chitosan Beadsmentioning
confidence: 84%
“…CH stretch vibrations were at 2921, 2871 cm −1 , COC—at 1071 cm −1 , 1649 cm −1 (amide I), 1554, 1599 cm −1 (amide II), and 1377 cm −1 (CH 3 ) (CH 3 CONH‐groups of chitosan). IR spectrum of CS‐coated magnetite particles was described earlier . In the spectrum of Fe 3 O 4 /CS/EM [Figure (A), 2 ] and IPEC CS/EM [Figure (B), 1 ] the absorption bands in the region of 1632–1708 cm −1 , ν COO − = 1555, 1400 cm −1 , and ν CO = 1074 cm −1 belonging to CS–MAC interpolyelectrolyte complex were presented earlier .…”
Section: Resultsmentioning
confidence: 70%
“…The dissolved chitosan was added dropwise on the magnetic fluid. Formed chitosan magnetic microspheres were washed with deionized water and soaked in 1, 3, and 5 mol % glutaraldehyde solution for 2 hrs and then washed with deionized water [17].…”
Section: Cross-linking Methodsmentioning
confidence: 99%